2011
DOI: 10.1174/021037011795377593
|View full text |Cite
|
Sign up to set email alerts
|

Usos, gestos y vocalizaciones privadas: de la interacción social a la autorregulación

Abstract: El papel del lenguaje en la autorregulación ha sido ampliamente estudiado. Sin embargo, hay escasa evidencia sobre la función de autorregulación de los sistemas semióticos prelingüísticos en el desarrollo temprano. Presentamos un estudio de diseño longitudinal para explorar cuándo y cómo los niños/as comienzan a utilizar signos prelingüísticos con una función de autorregulación. Observamos a cuatro bebés en interacción con un adulto y un objeto complejo, a los 11, 13 y 15 meses de edad. Se condujo un análisis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 15 publications
2
18
0
11
Order By: Relevance
“…In previous research (Basilio & Rodríguez, 2011;Rodríguez & Palacios, 2007) we found that observing children and parents interacting with complex objects that involve challenging clear goals is an optimal situation for studying self-regulation in the preverbal stage, developing reliable indicators based on communicative behaviours, and characterising parental mediation. These interactions can also be characterised as playful in nature, given that (a) for infants the concept of a 'task' is not yet graspable, and (b) parents behaviours involve characteristic play cues (Lillard, 2007).…”
Section: Theoretical Approach: Cognitive Self-regulation and Early Sementioning
confidence: 94%
See 2 more Smart Citations
“…In previous research (Basilio & Rodríguez, 2011;Rodríguez & Palacios, 2007) we found that observing children and parents interacting with complex objects that involve challenging clear goals is an optimal situation for studying self-regulation in the preverbal stage, developing reliable indicators based on communicative behaviours, and characterising parental mediation. These interactions can also be characterised as playful in nature, given that (a) for infants the concept of a 'task' is not yet graspable, and (b) parents behaviours involve characteristic play cues (Lillard, 2007).…”
Section: Theoretical Approach: Cognitive Self-regulation and Early Sementioning
confidence: 94%
“…If this was indeed the case, the uses of gestures for cognitive purposes could be considered an early mechanism by which interactions with others influence cognitive development, especially in relation to the development of selfregulation. However, only a handful of case studies have provided evidence of this cognitive function of gestures in children of 2 years and under (Rodríguez & Palacios, 2007;Vallotton, 2008;Rodríguez, 2009;Basilio & Rodríguez, 2011).…”
Section: Early Communicative Skills Parental Interaction and Early mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Basilio, & Sosa [2015]; Rodríguez & Moro [1999. A2: Basilio [2014]; Basilio & Rodríguez [2011; Dupertuis & Moro [2016]; Moro, Dupertuis, Fardel, & Piguet [2015]; Moro & Rodríguez [2005 Alessandroni/Rodríguez the mother and the child; (c) gestures performed by the mother and the child; (d) language used by the mother; (e) vocalizations made by the child, and (f) containercenter-of-the-action (CCA) in each moment, for the mother and the child. A CCA is an object that functions as a container and that, in a given moment, acts as the locus around which the actions of the child, the mother or both are organized.…”
Section: Methodsmentioning
confidence: 99%
“…The complexity and importance of this milestone are clear: to use an object by its function (i.e., any spoon as a spoon) implies a qualitative jump for the child, every time he stops relating to isolated materialities and starts relating to members of classes [Rodríguez, 2012a]. Furthermore, conventional uses of objects become the base upon which symbolic uses [see Alessandroni, 2016;Palacios & Rodríguez, 2015;Palacios et al, 2016;Rodríguez, Palacios, Cárdenas, & Yuste, 2014], and cognitive self-regulation behaviors [Basilio & Rodríguez, 2011 …”
mentioning
confidence: 99%